1992
DOI: 10.1115/1.2928036
|View full text |Cite
|
Sign up to set email alerts
|

Film Cooling on a Gas Turbine Rotor Blade

Abstract: The film cooling effectiveness on a low-speed stationary cascade and the rotating blade has been measured by using a heat-mass transfer analogy. The film cooling effectiveness on the suction surface of the rotating blade fits well with that on the stationary blade, but a low level of effectiveness appears on the pressure surface of the rotating blade. In this paper, typical film cooling data will be presented and film cooling on a rotating blade is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(27 citation statements)
references
References 0 publications
1
25
1
Order By: Relevance
“…Dring et al (1980) reported film cooling effectiveness in a rotating configuration in a low speed tunnel. Takeishi et al (1992) also studied film cooling effectiveness on a stator-rotor stage, simulating a heavy duty gas turbine. Measured effectiveness values on the suction side for the rotating turbine blade seemed to match the data from the stationary cascade; whereas the rotating effectiveness on the pressure side seemed to be significantly lower than the nonrotating case.…”
Section: Film Cooling Under Rotating Conditionsmentioning
confidence: 99%
“…Dring et al (1980) reported film cooling effectiveness in a rotating configuration in a low speed tunnel. Takeishi et al (1992) also studied film cooling effectiveness on a stator-rotor stage, simulating a heavy duty gas turbine. Measured effectiveness values on the suction side for the rotating turbine blade seemed to match the data from the stationary cascade; whereas the rotating effectiveness on the pressure side seemed to be significantly lower than the nonrotating case.…”
Section: Film Cooling Under Rotating Conditionsmentioning
confidence: 99%
“…The results show that the calculated value is lower in most cases, but that the deviations are acceptable. Takeishi et al [3] studied the superposition effect of film cooling effectiveness for multi-row holes on a turbine blade. The results show the Sellers' method is suitable for the suction side of the vane, and only suitable for a rotating working blade far downstream of the film cooling holes.…”
Section: Introductionmentioning
confidence: 99%
“…At the reference speed of 2,550 rpm, the rotor platform has the maximum cooling effectiveness and coolant coverage. Takeishi [3] measured the film cooling effectiveness on a rotor blade using the heat-mass transfer method. On the suction side, the film cooling effectiveness fits well with that in stationary cascade, but is lower than that in stationary on the pressure side.…”
Section: Introductionmentioning
confidence: 99%